Examining the Impact of Antecedents of Firm Performance on Companies in South Africa - Chinomona, Elizabeth (Journal of Economics and Behavioral Studies, 2019)
The aim of this study is to establish the impact of social media, information sharing and knowledge sharing on firm performance among companies in South Africa, Gauteng province in particular. In as much as the issue of social media communication has received great benefits and growth within organisations, little has been researched about the impact of social media on job performance, knowledge sharing and information sharing among companies in the Gauteng province, South Africa. Social Identity Theory (SIT) has been used to explain the associations in the model. Questionnaires were distributed to both management staff and lower level employees in the companies in Gauteng province of South Africa. This study used a quantitative research methodology using Smart PLS software. This software was employed to test the relationships among the four hypotheses. The results showed that there is a positive and significant relationship among the four proposed hypotheses. Basing on the findings of this research, recommendations were made to both the top-level employees and lower level employees in the companies in South Africa. This study is expected to have real-world and academic implications to policymakers for the companies in South Africa. On top of this, the study will provide new insights and added first-hand knowledge to the existing body of literature which is meagre in South African companies.